Naiset ja oikeusavun unohdettu historia - Vasara-Aaltonen, Marianne (Lakimies, 2024)
Women and the forgotten history of legal aid Using diverse primary sources, this article examines the connection between the women’s movement and the organisation of legal aid in Finland. As industrialisation and urbanisation increased in the 19th century, the need for legal aid also grew among the working class. Therefore, legal aid was organised also in Finland when, in the 1880s, Helsinki decided to employ an advocate for the poor. The research shows that the Finnish Women’s Association played an important part in the establishment of legal aid in Helsinki, as it actively lobbied for the employment of an advocate for the poor. The underlying idea was that legal aid would especially benefit poor women. Legal aid statistics show that, in fact, the majority of clients were women. The article discusses the topic also in a comparative context. The interest Finnish women displayed in legal aid can be seen as part of an international phenomenon where the women’s movement tried to further women’s rights also through legal aid. Finnish women’s rights activists had active international contacts which made it possible for them to gain information also on the organisation of legal aid in other countries.